Implementation of Citizenship Education as a Complete Philosophical - Artika Sari (International Journal of Students Education, 2024)
This research examines the implementation of citizenship education philosophically. The aim of this research is to gain experience on how to implement idealistic philosophy education in elementary schools, so that this research is expected to contribute to overcoming the problems that exist in the world of education. This research is qualitative research with the character of a library research using and exploiting books and other literature as the main object (Hadi, 1995: 3). This type of qualitative research is research that produces information in the form of notes, descriptive data contained in the text being studied. In this research, the literature study method was used. The data collection technique used is by reviewing literature, books, notes and various reports related to the elements and philosophy of education. The results of the research show that students have the status of learning subjects, the person who guides (educator) is the person who is responsible for the implementation of education targeting students, the interaction between students and educators (educative interaction), the direction in which guidance is aimed (educational goals) tools and methods are everything that is done, carried out deliberately to achieve educational goals.